2010
DOI: 10.1007/s11746-010-1709-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Grape Seed Extracts on the Physicochemical and Sensory Properties of Corn Chips during Storage

Abstract: This study evaluated the effectiveness of grape seed extracts (GSE) on lipid oxidation of corn chips stored for 90 days in comparison to tert-butylhydroxytoluene (BHT). Proximate chemical analysis results showed that corn chips contained low moisture contents (less than 2%) and also that no significant differences were found in the dry matter values in ash, fat, protein, and fiber. Antioxidant activity of the GSE measured by an oxidative stability instrument ranged from 1.6 to 9.3 h of induction time, while BH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
5
11
0
Order By: Relevance
“…Our research demonstrated that corn crisps enriched in 5 % with linseed oil are stable for 6 months in barrier packaging filled with argon. Their performance in packages filled with atmospheric air is significantly worse and in this regard the results of our studies differ from those of Shaviklo et al [54,55], but at the same time, they are concordant with the research by Rababah et al [68]. The usage of argon as the atmosphere modifier in the packaging is caused by the fact that it is almost completely chemically passive, creating only unstable hydrates Ar · 6H 2 O.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Our research demonstrated that corn crisps enriched in 5 % with linseed oil are stable for 6 months in barrier packaging filled with argon. Their performance in packages filled with atmospheric air is significantly worse and in this regard the results of our studies differ from those of Shaviklo et al [54,55], but at the same time, they are concordant with the research by Rababah et al [68]. The usage of argon as the atmosphere modifier in the packaging is caused by the fact that it is almost completely chemically passive, creating only unstable hydrates Ar · 6H 2 O.…”
Section: Resultssupporting
confidence: 84%
“…They also observed a high oxidation and sensory stability in corn crisps containing as much as 28 % of fatty fraction without the addition of antioxidants, which were stored for 90 days in OPP packages filled with atmospheric air. Rababah et al [68] studied the oxidation stability as well as quantitative and qualitative changes in the sensory profile of corn crisps enriched with grape seed extract. Their research showed that the addition of synthetic antioxidants (BHT 200 ppm) as well as the addition of grape seed extract in the amount of 400 and 800 ppm contribute to the significant increase of chemical quality and preservation of the original qualitative and quantitative sensory profile of corn crisps containing approximately 5 % of fatty fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Wine pomace also successfully inhibited lipid oxidation in dairy products such as yogurt (Ersöz and others ) and cheese (Shan and others ), and in vegetable‐derived products such as corn (Rababah and others ) and potato chips (Rababah and others ).…”
Section: Functions In the Food Industrymentioning
confidence: 98%
“…In this industry, major products are chips, which account for 45% of total industry revenue (Statista, 2020). Despite the high interest in them, the chips are always under speculation for their poor nutritional value; hence recent research efforts have focused on the reformulation of chips with functional components such as plant extracts, legumes, cereals, dietary fiber, etc., (Kayacier, Yüksel, & Karaman, 2014; Mendonca, Grossmann, & Verhé, 2000; Onwulata, Konstance, Strange, Smith, & Holsinger, 2000; Rababah et al., 2011). Moreover, most commercial chips produced by frying contain high amounts of oil, which has a negative effect on conscious consumers who prefer healthy foods.…”
Section: Introductionmentioning
confidence: 99%